Integraç\~ao de registros administrativos para políticas de proteç\~ao social: Contribuiç\~oes a partir da experiência brasileira - Letícia Bartholo; Joana Mostafa; Rafael Guerreiro Osorio (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– Integrating information for the purpose of articulating social protection policies is hard work. It takes from political will, to capacity for institutional cooperation, to software development and direct communication channels with citizens. Because of that complexity, countries that pursue this objective often cooperate to exchange knowledge and the Brazilian case of Cadastro Único (Single Registry), the backbone of some 20 social protection programs, is frequently cited as a success case of integration. By means of the Cadastro Único experience, this text debates some of the essential elements to constitute such instruments of social policy integration. Bringing to light some of the challenges that are still on the way, to fulfill the promise of greater integration amongst social protection programs, as well as provide greater ease of access and respect to citizens.
Keywords: I38; 330; Cadastro Único; Bolsa Familia program; Unified Registry; Assistance; Entitlements; Family Allowances; Food Stamp; Means Testing; Poverty Alleviation; Public Assistance; Safety Net; Social Welfare Programs; SSI; Transfer Payments; Transfers; Welfare Effects; Welfare Policy; Welfare Program; Welfare Provision; Work Welfare